Distributed Transformers for Broadband Monolithic Millimeter-Wave Integrated Power Amplifiers - Pahl, Kai-Philipp Walter (KIT Scientific Publishing, 2015)
This work presents methods and techniques to optimize and implement distributed magnetic transformers for their application in matching networks of Monolithic Millimeter-wave Integrated Circuits (MMICs). It describes strategies for the efficiency and bandwidth optimization of the transformers and demonstrates their potential based on an optimized transformer geometry as well as two MMIC power amplifiers.
English
Keywords: power amplifier; Leistungsteiler; Impedanztransformator; power divider/combiner; millimeter-wave; Millimeterwellentechnik; Leistungsverstärker; Monolitische Integrierte Millimeterwellenschaltung (MMIC)Impedance transformer; Monolithic Millimeter-wave Integrated Circuit (MMIC)